Training interpreters to work with foreign gender violence victims in police and court settings - Pozo-Triviño, Maribel Del; Toledano-Buendía, Carmen (Language and Law / Linguagem e Direito, 2017)
Violence against women is a type of gender based discrimination suffered by women all over the world and it aects dierent groups of women in different ways. Migrant women who do not speak the host country language are especially vulnerable due to their cultural, social and linguistic isolation. To guarantee their rights, governments have an obligation to provide means for such victims to understand and be understood, including the provision of quality translation and interpreting. This paper denes the characteristics of police and court interpreting for gender violence (GV) victims and ascertains the training needs of interpreters to work in these contexts. Fieldwork results from the SOS-VICS1 Project were analysed, including the questionnaire and interviews with agents2 working with GV victims, as well as the survey carried out on interpreters providing attention to victims. The results conrm that interpreters require specialised training for their role in building communication bridges between the public services and the victims.